TRAINING OF FUTURE SPECIALISTS IN PRESCHOOL EDUCATION FOR THE FORMATION OF THE ACTIVITY OF PRESCHOOL CHILDREN - Lazarovych, Nadiya (Theoretical and Methodical Problems of Children and Youth Education, 2023)
In the article, the problem of training future educators for the development of research activity of older preschoolers is revealed, research analysis is carried out, features of the development of research activity of preschoolers are identified, theoretical approaches to understanding the concept of “research activity” are revealed. To solve the above-mentioned problem, theoretical methods of analysis and synthesis of theoretical and scientific-methodological sources from psychology, pedagogy were used to develop the main concepts of the research on the training of future specialists in the preschool field for the formation of the activity of preschool children. We consider the concept of “research activity” as a persistent desire of the personality of a child of older preschool age to realize, with the help of search activity, the need to learn about the objects of the surrounding world and to discover new knowledge for him. The attention of future educators is drawn to the structure (acceptance of a cognitive task; putting forward hypotheses for obtaining results; selecting methods and planning to achieve results; checking the chosen method of putting forward assumptions) and characteristic features of the development of research activities in preschool childhood (at 5–6 years of age, a child begins to develop selectivity of research activity that ensures the child’s constant openness to new things, which is expressed in the search for inconsistencies and contradictions). We see the competence of a teacher in successfully solving interrelated tasks: seeing a child in the educational process, creating conditions for the successful development of research activity, achieving educational goals, effectively interacting with children and other subjects of education, organizing and using a developmental educational environment. The training of future educators involves the development of the necessary skills and abilities needed to organize the process of developing the research activity of preschoolers. In the process of implementing the theoretical principles of training future educators for the development of preschoolers’ research activity, a business game “The role of the subject-developmental environment in the development of research activity of older preschoolers” was held in a preschool education institution. Ensuring the quality of the educational process for the development of research activity of older preschoolers requires the need to increase the theoretical, practical, organizational and methodological training of future teachers in a higher education institution.